Impact of COVID-19 lockdown on Serie A soccer players` physical qualities - Rampinini, E.; Donghi, F.; Martin, M.; Bosio, A.; Riggio, M.; Maffiuletti, N. A. (International Journal of Sports Medicine, 2021)
In March 2020, the COVID-19 pandemic forced most activities in Italy, including soccer, to cease. During lockdown, players could only train at home, with limited evidence regarding the effect of this period. Therefore, this study aimed to investigate the effect of COVID-19 lockdown on professional soccer players` physical performance. Aerobic fitness and vertical jump were assessed before and after four periods in two different seasons: COVID-19 lockdown, competitive period before lockdown, competitive period and summer break of the 2016-2017 season. Linear mixed models were used to examine within-period changes and between-period differences in changes observed during COVID-19 lockdown and the three other periods. Within-period changes in aerobic fitness showed a significant improvement following COVID-19 lockdown (p<0.001) and a significant decline during summer break (p<0.001). Between-period differences were significant in the comparison of COVID-19 lockdown with both the competitive 2019-2020 season (p<0.01) and summer break (p<0.001). For the vertical jump, only the between-period comparison revealed significant differences as the changes associated with COVID-19 lockdown were worse than those of the two competitive periods, for both absolute (p<0.05; p<0.001) and relative peak power (p<0.01; p<0.001). Home-based training during lockdown was effective to improve aerobic fitness, although it did not allow players to maintain their competitive period`s power levels.